American foundations in the Great Bear Rainforest: Philanthrocapitalism, governmentality, and democracy - Tedesco, D (Geoforum, 2015)
This is the author accepted manuscript. The final version is available from Elsevier via the DOI in this record. Environmental campaigns to save the Great Bear Rainforest (GBR) in British Columbia, Canada faced complex ecological, socio-economic, and political challenges that made traditional models of protected areas unfeasible. Between 2001 and 2007, the Government of British Columbia announced commitments to a series of conservancies, to “government-to-government” negotiations with First Nations, and to ecosystem-based management and sustainable development in the remaining region, supported by a $120 million Conservation Opportunities Fund (COF). This innovative policy solution developed out of complex negotiations between ENGOs, industry, First Nations, local communities, and the province. American charitable foundations funded the campaigns of environmental nonprofit organizations (ENGOs) and contributed substantial amounts to the conservation-financing fund. While their role is frequently noted, it has not been adequately studied. Engaging the scholarly and professional conversations about the neoliberal underpinnings of philanthrocapitalism or venture philanthropy, I argue that the lens of governmentality – the techniques and rationalities of governance that produce and normalize patterns of thought and behavior – draws attention to discursive as well as financial circulations, to agonistic relations and negotiations, and to processes of inclusion and exclusion. I then trace the circulation of financial resources and discursive representations between foundations and ENGOs between 1997 and 2007. Given concerns that neoliberal philanthropy may narrow ENGO campaigns and conservation solutions to those most amenable to market relations and may institutionalize neoliberal rationalities within recipient organizations, this paper raises crucial questions about the growing adherence to philanthrocapitalism within the foundations involved and the formation, articulation, and inclusion/exclusion of ENGO voices ...